A pre-experimental study to evaluate the effectiveness of back massage among pregnant women in first stage of labour pains admitted in labour room of a selected hospital, Ludhiana, Punjab, India - Sethi, Deepika; Barnabas, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Labour is a health state that most women aspire to, at some point in their lives. The first thought that comes to the mind of an expecting woman regarding her delivery is the pain of labour. The major role and responsibility of the nurse is in identifying the problems of the woman in labour, providing appropriate information regarding the alternative modalities of pain relief during labour. A pre-experimental study was conducted to evaluate the effectiveness of back massage on pain among pregnant women in first stage of labour pains in a selected Hospital, Ludhiana, Punjab. The objectives of the study were to assess the pre-test level of pain in first stage of labour pains among pregnant women, to administer the back massage in first stage of labour pains, to assess the post-test level of pain and to compare the pre-test and post-test level of pain in first stage of labour pains among pregnant women and to determine the relationship of pre-test and post-test level of pain with the selected variables. Methods: Conceptual framework was based on General system theory by Ludwig Von Bertanlanffy. Modified Labour Pain Relief Tool and Participants Opinionnarie were used to assess the effectiveness of back massage. Results: Findings of the study were in the pre-test mean score was 5.83 and post-test mean score was 3.75 which was found statistically highly significant at p<0.01 level. Gravida had significant impact on level of pain. Back massage had impact on level of pain among pregnant women. Conclusions: Present study revealed that in the pre-test mean score was 5.83 and post-test mean score was 3.75 which was found statistically highly significant at p<0.01 level. Age, education, mother’s occupation, period of gestation and any history of abortion had no significant relationship with pain, and gravida had statistically significant relationship with pain. Back massage had impact on pain level. Therefore it was concluded that back massage was effective to reduce the level of pain.